Kilam û jin - Çifçi, Tekin (Nûbihar, 2014)
Woman in Kurdish folklore and folk songs; history and criticism
Originally presented as author's thesis (masters)–Mardin Artuklu University
Keywords: Hochschulschrift; Folk poetry; Kurdish; Folk songs; Kurdish; Women; Women; Kurdish